LEGAL ANALYSIS OF THE LAW OF THE REPUBLIC OF UZBEKISTAN “ON PAYMENTS AND PAYMENT SYSTEM” (TSUL LEGAL REPORT, 2026)
This paper examines Uzbekistan’s legislation governing payments and payment systems, Law No. LRU-578, enacted on November 1, 2019. It provides background on the law’s objectives of regulating relationships around payment services among individuals and entities. The aim is to assess key provisions concerning system operators, participant roles, licensing, risk management, settlement finality, electronic money, security protocols, and Central Bank oversight. Methodologically, the law’s text is reviewed to summarize directives and elucidate concepts. Results detail defined terms, system categorization, operator functions, settlement irrevocability, licensing procedures, electronic currency parameters, risk mitigation, incident reporting, and non-compliance penalties. While underscoring integrity, efficiency, and oversight of payment systems, certain technology-based transactions are excluded. Recommendations include ensuring comprehensive coverage in line with global frameworks, emphasizing consumer protection, and addressing emerging electronic platforms. As digital payments growth accelerates globally, analysis of Uzbekistan’s updated legal basis and directions for further strengthening are pertinent.